Ergonomic-Based Redesign of Broomsticks Reduces the Physiological Burdens of Street Sweepers in Denpasar City, Indonesia - Palilingan, Richard Andreas; Tirtayasa, Ketut; Surata, I Wayan (Jurnal Ergonomi Indonesia (The Indonesian Journal of Ergonomic); Vol 6 No 2 (2020): Volume 6 No 2 Desember 2020, 2020)
The equipment, such as broomsticks used by street sweepers are not appropriate based on anthropometric aspects, with a potency to induce inconvenience among them. Working with equipment that is not ergonomics, in addition to non-physiological work posture can cause fatigue, musculoskeletal disorders, and increased workload. This study aims to determine whether redesign an ergonomic-based broomstick may reduce the physiological burden of street sweepers in Denpasar city, Indonesia. This research is a pure experiment using a cross-design (two-period crossover design). The sample was 16 female street sweepers, divided into two groups: 8 as the control group and 8 treatment groups. Data analysis were performed using a paired t-test with significance level of 5%. The results showed significant difference (p <0.05) on the variables of workload, musculoskeletal complaints, and fatigue. In the first period, the mean of the street sweeper working heart rate was 118.96 ± 2.26 beats per minutes (bpm), the mean musculoskeletal complaint score was 91.63 ± 2.70 and the average fatigue was 77.69 ± 2.96. In Period II, the mean heart rate was 98.49 ± 2.22 bpm, the mean musculoskeletal complaint score was 63.56 ± 2.73 and the average fatigue was 57.56 ± 2.94. Redesigned stem brooms turned out to reduce workload, musculoskeletal complaints, and fatigue by 17.21%, 30.6%, and 25.91%, respectively. It can be concluded that the redesign of an ergonomic-based broomstick can reduce workload, musculoskeletal complaints, and fatigue.